The relationship between radiographic disc calcification score and FGF4L2 genotype in dachshunds - Stacey Sullivan; David Redden; Froydis Hardeng; Malin Sundqvist; Michelle Kutzler (Journal of Veterinary Internal Medicine)
Abstract Background The relationship between radiographic disc calcification score and FGF4L2 genotype has been reported in only a small number of dachshunds. Hypothesis A genotype with either 0 or 1 FGF4L2 copy will be associated with a lower number of calcified discs (lower K‐n) compared with a genotype with 2 FGF4L2 copies. Animals Dachshunds registered with the Norwegian or Finnish Kennel Clubs for which both K‐n and FGF4L2 genotype are known (n = 407). Methods Retrospective study (2012‐2024). The frequency and percentage of dachshunds within each K‐n group (K0, K1/2, K3/4, K5+) by FGF4L2 genotype (FGF4L2/FGF4L2, N/FGF4L2, N/N) were reported. The K‐n distribution differences among genotypes were analyzed by the Cochran‐Mantel‐Haenszel test in SAS 9.4. Significance was defined as P < .05. Results A difference in K‐n distribution was found between dachshunds that have 0 or 2 FGF4L2 copies. However, no difference was found in the K‐n distribution between dachshunds that have 1 or 2 FGF4L2 copies. Conclusions and Clinical Importance Most dachshunds with 1 FGF4L2 copy have radiographic disc calcification scores that are associated with substantially lower risk of symptomatic disc disease. Radiographic disc calcification scores are similar in dachshunds with 0 and 1 FGF4L2 copies. Given the high allele frequency of FGF4L2, breeding to produce progeny with 1 FGF4L2 copy is expected to be a more achievable short‐term goal for dachshund spinal health breeding programs than breeding for 0 copies. It is recommended that both K‐n and FGF4L2 genotype status be considered when choosing dachshund breeding stock.